Influence of the replacement of ungraded-PKS aggregate on properties of lightweight pervious concrete - Mohd Faizal, Md Jaafar; Norhaiza, Ghazali; Khairunisa, Muthusamy; Ezahtul Shahreen, Ab Wahab; Azlina, Ismail (Penerbit Universiti Malaysia Pahang, 2021)
Pervious concrete is not environmentally friendly due to presences of non-renewable material in its production. Pervious concrete has made a comeback as a green infrastructure and researchers came up with a proposal to use waste materials that potentially to work well as material in pervious concrete. The used of palm kernel shell (PKS) in pervious concrete is consider brilliant because Malaysia is of the larger oil palm producer in the world. In this study, natural aggregate was partially replaced by 0, 10, 15, and 20% by weight of PKS aggregate to produce lightweight pervious concrete based PKS. The testing conducted comprise of density, void content, compressive strength, and flexural strength. Inclusion of PKS aggregate reduces the mechanical properties of pervious concrete but significantly higher than recommended in the standard, utilizing some PKS aggregate as partial aggregate at up to 20% substitution level can produce lightweight PKS-pervious concrete. The pervious concrete containing 10% of PKS aggregate presented the most optimum mixture. Besides, the use of PKS as aggregate replacement in pervious concrete mixture indicates a good potential towards sourcing alternative sustainable materials for concrete.